Origin of the active luminescence from Sm3+-activated borate phosphors: a correlational study of trap states and decay kinetics. (20th December 2022) - Anitha, N.; Jayanthi, K.; Rakshita, M.; Sharma, Aachal A.; Jayarambabu, N.; Akshaykranth, A.; Babu, Kishore; Rao, T. Venkatappa; Dinakar, D.; Haranath, D.
Abstract : A series of Sm 3+ -activated strontium hexaborate (SrB6 O10 ) red phosphors has been synthesized using a soluble salt reaction (SSR) method and the correlation between their trap states and decay kinetics was studied in detail. Abstract : The photoluminescent (PL) properties of Sm 3+ -doped strontium hexaborate (SrB6 O10 ) phosphors are significantly influenced by their crystallinity, phase and dopant concentration. To obtain a high brightness orange-red emitting SrB6 O10 :Sm 3+ phosphor, a controlled and modified soluble-salt reaction method in the presence of a chelating agent (citric acid, C6 H8 O7 ) was used at ∼700 °C for about half an hour under an air atmosphere, which is otherwise only possible at very high (>1500 °C) sintering temperatures. The PL spectrum of the SrB6 O10 :Sm 3+ phosphor produced strong and intense PL emission peaks centered at 560 nm ( 4 G5/2 → 6 H5/2 ), 596 nm ( 4 G5/2 → 6 H7/2 ), and 640 nm ( 4 G5/2 → 6 H9/2 ) under excitation of 400 nm ( 6 H5/2 → 6 H7/2 ). This is one of the very few reports that depicts the formation of more shallow traps in the lattice and the concentration quenching phenomenon was attributed to the non-radiative transfer of energy among Sm 3+ ions via dipole–dipole interactions in the trap states. The optimized phosphor has noticeable reddish-orange Commission International de I'Eclairage color coordinates of (0.459, 0.337). The PL decay kinetics of the synthesized phosphor showed a biexponential decaying characteristic with an overall decay time of milliseconds. The presence of borate ions benefitted the thermal stability of the SrB6 O10 :Sm 3+ phosphor as well. X-ray diffraction studies confirmed the phase purity, while scanning electron microscopy revealed the morphology to be an agglomerated rod-like structure. The PL intensity increased with increasing Sm 3+ concentration and reached the optimum at 0.1 mol%. The obtained results clearly indicate that the SrB6 O10 :Sm 3+ phosphor is a viable material for providing a red component for white-light emitting diodes (w-LEDs).